The role of socio-cultural and religious factors in peace building the case of ingushetia (Russian Federation) - Oziev, Gapur (Hena e Plote Beder University Faculty of Humanities, 2014)
Ingushetia is one of the states of southern part of the Russian Federation with population is less than half a million and it is predominantly a Muslim state. Up to date the local ethnic Ingushs strictly follow and live in a tribal system which they inherited from their ancestors. Throughout the history, Ingushs have demonstrated their own mechanism of reconciliation and peace building process in case of tribal conflicts. The local socio-cultural and religious factors have always played extremely effective role in preserving a harmonious life among various tribes as well as communities in Ingushetia. Interestingly, in most cases, this mechanism has proven to be more efficient and productive than the existing state law. This paper has adopted a descriptive method of analysis. The findings are expected to reveal the major factors which helped Ingushs to preserve their identity unchanged throughout their history.